2021
DOI: 10.1111/cch.12903
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and difficulties in children with specific learning disabilities

Abstract: Background: The study aims to investigate the social, emotional, and behavioral challenges in children with a specific learning disability (SLD) and to identify the factors that accompany these problems by screening with the Strengths and Difficulties Questionnaire (SDQ). Methods:The descriptive study was conducted on 278 children with SLD. Strengths and difficulties in children were evaluated by the SDQ applied to their mothers. The percentage of cases above the cut-off limits of the SDQ was calculated. Chi-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Mogasale et al [33] found a higher percentage of parents of students with learning disabilities including dysgraphia had an institute and higher level. However, in a study conducted in 2022 in Turkey, the difference was more significant for low mothers' education [34].…”
Section: Figure 1 the Prevalence Of Dysgraphic Studentsmentioning
confidence: 85%
“…Mogasale et al [33] found a higher percentage of parents of students with learning disabilities including dysgraphia had an institute and higher level. However, in a study conducted in 2022 in Turkey, the difference was more significant for low mothers' education [34].…”
Section: Figure 1 the Prevalence Of Dysgraphic Studentsmentioning
confidence: 85%
“…The use of the SDQ scale in this study demonstrates that this assessment tool can be used in the area of ongoing monitoring of emotional problems and reading motivation in children with Dyslexia, in addition to identifying children with Dyslexia. In a further surprising finding, researcher Ayar and colleagues used the SDQ scale in a study of 278 school-aged children with specific learning disabilities (SLD), and the results showed that the SDQ scale was able to accurately determine whether the children had SLD (Ayar et al, 2022). According to the DSM-5 criteria (American Psychiatric Association Division of Research, 2013), SLD includes not only Dyslexia, but also dysgraphia, dyscalculia, and visual This means that the SDQ scale is also accurate in determining other types of specific learning disabilities.…”
Section: Content the Current Study Of Cognitive Assessment Of Dyslexiamentioning
confidence: 99%
“…Therefore, in pre-school years, it is necessary to focus on the language development of the child and to prepare teaching-learning environments that will support his/her language development. The quality of the experiences that a child gains during these ages will certainly affect his/her learning experiences in the following years (Hills et all, 2010;Yalcin, 2010).…”
Section: Introductionmentioning
confidence: 99%